2011
DOI: 10.3171/2011.1.focus10303
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operative failure of endoscopic third ventriculostomy in pediatric patients: the role of cine phase-contrast MR imaging

Abstract: Object Although a rarely reported occurrence, late failure of endoscopic third ventriculostomy (ETV) may occur in children as a result of a variety of factors. Delay in recognition of symptoms can lead to harmful deterioration in the patient's condition. The authors undertook this study to assess the capacity of cine phase-contrast MR imaging to identify late failure in asymptomatic pediatric patients treated with ETV for hydrocephalus. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…2,12,19,50,52,67,69 A thicker third ventricle floor has been negatively associated with ETV success, 59 but unfortunately we could not retrospectively analyze this aspect. The presence of cisternal scarring has been negatively associated with success of the first ETV.…”
Section: Intraoperative Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…2,12,19,50,52,67,69 A thicker third ventricle floor has been negatively associated with ETV success, 59 but unfortunately we could not retrospectively analyze this aspect. The presence of cisternal scarring has been negatively associated with success of the first ETV.…”
Section: Intraoperative Findingsmentioning
confidence: 95%
“…40 Although the comfort of parents could be a reason to prefer ETV over shunting, it can also make parents less cautious (i.e., provide a false sense of security), as there is no certainty of a cure for hydrocephalus, and late failure of ETV does occur with potential devastating results. 14,19,27,60 In our study, the latest failures occurred 12 years after ETV and 8 years after re-ETV.…”
Section: Effect Of Timementioning
confidence: 99%
See 1 more Smart Citation
“…Cine PC MRI may be used to determine the patency of the stoma and may be used in follow-up. 4,24,30,31 Determining the best candidates for ETV has been difficult, with conflicting reports on who are the best candidates, particularly regarding the effect of age and etiology. Reports have indicated that outcome is a function of age 23,32,33 independent of age, 1,34 a function of etiology, 1,35-37 or a function of both age and etiology.…”
Section: Discussionmentioning
confidence: 99%
“…23 Intraoperative observation of thickened arachnoid membranes at the level of the interpeduncular cisterns at the time of ETV should be considered a significant risk of stoma block. 24 Postoperative failures usually occur early; regular clinical and radiologic follow-up must be performed, especially in the first years after the ETV. 25 According to Mohanty et al, 26 reclosure of the stoma because of gliosis and scarring has been observed in 6 to 15% of ETV failures.…”
Section: Discussionmentioning
confidence: 99%